DIFFERENT LIGHT DENSITY FLUX IN ORGANOGENESIS OF YELLOW PASSION FRUIT - da COSTA, Cristiane Maria; AYUB, Ricardo Antonio (Scientia Agraria, 2002)
The crops problems that pass intensive passion fruit culture, like fungal and bacterial disease, lake of productivity varieties, carry us to think in the biotechnologys uses to solve this problems. In order to evaluate the effect of different light intensity in the organogenesis of yellow passion fruit, an essay was conducted at biotechnology lab. at UEPG, PR, Brazil. The medium used was MS supplemented with B5 vitamin complex, 30 g.L-1 sucrose, 100 mg.L-1 de inositol, 1 mg.L-1 BAP and solidified with 2,6 g.L-1 Phytagel. The experimental essay was in a randomized blocks, and the treatments corresponded the light intensity 0,25 ìmol. m-2. s-1; 6 ìmol. m-2. s-1; 7 ìmol. m-2. s-1; 9,75 ìmol. m-2. s-1; 10,88 ìmol. m-2. s-1 e 32,5 ìmol. m-2. s-1 provide by white cold lamp (110W) with five repetitions. The statistical analyses were realized with Estat program from UNESP - Jaboticabal, SP. We analyzed the percentage of explantes with shoots and the number of shoots per explantes. The best morphogenetic answer for the number of explantes with shoots and the number of shoots per explantes are achieved with 9,75 ìmol. m-2. s-1, however low light intensity arent a problem in tissue culture of passion fruit.